(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The dynamics between original texts and their translations have traditionally been conceptualized within hierarchical frameworks, under which the "original" is seen as the authoritative and authentic text, and translations are viewed as derivative, secondary, or auxiliary. This research challenges that dominant perspective by examining how translation can operate not just as an inferior product but as an equally valid, or in some cases, a more powerful textual form. Drawing on the insights of literary theory, translation studies, and intercultural communication, this research examines situations in which translations have distinctive receptions, achieve canonical status, or surpass their originals in effect. Through the close examination of both historical and contemporary cases, the research focuses on situations where translation produces cultural value, challenges authorial control, and builds competing textual realities. The research shows that what is between "original" and "translation" becomes increasingly more unstable under conditions of multilingualism and globalization. Accordingly, a relational approach is developed whereby the translational and original exist within a mutually dependent and productive relationship, precipitating a move from originality to an examination of processes involved in textual circulation, reception, and meaning-making.